Perancangan Laporan Keuangan Berdasarkan ISAK 335 Studi Kasus Yayasan Xyz Menggunakan Ms.Excel - Nicolas; Etty Gurendrawati; Ayatulloh Michael Musyaffi (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to design financial statements based on Interpretation 335 of the Financial Accounting Standards at the XYZ Foundation. The urgency of this study stems from the still-low level of adoption of financial reporting standards among nonprofit organizations, particularly with regard to Interpretation 335, which has the potential to lead to a lack of transparency and accountability in financial management. Additionally, there is a research gap in the form of the lack of practical guidelines or templates that foundations can use to prepare financial statements in accordance with applicable standards. This study employs a Research and Development (R&D) methodology using the ADDIE model, with a focus on the development phase. Data was collected through interviews with the foundation’s treasurer and secretary. The data analysis technique used in this study is qualitative descriptive analysis. The XYZ Foundation has not yet implemented or prepared financial reports in accordance with these standards. The results of this study produced a financial reporting template in accordance with Interpretation 335 of the Financial Accounting Standards, consisting of a Statement of Financial Position, a Statement of Comprehensive Income, a Statement of Changes in Net Assets, a Cash Flow Statement, and Notes to the Financial Statements.